2014
DOI: 10.5455/ijmsph.2014.220820142
|View full text |Cite
|
Sign up to set email alerts
|

A six year retrospective study of maternal mortality at a tertiary teaching institute in Uttarpradesh

Abstract: Background: A high maternal mortality ratio is a serious public health issue in India. The lack of monitoring of pregnant mothers contributes to maternal deaths. Aims & Objectives: This To study the incidence of maternal mortality and the causes of maternal mortality at a tertiary care (teaching) institute over a period of 6 years from January 2006 -December 2010. Materials and Methods: A retrospective analysis of maternal deaths from hospital records. Results: As per present study, MMR was 1180 per 100,000 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
2
10
1
Order By: Relevance
“…In this study, we included only those cases which were given some kind of resuscitative measure in intensive care unit or in labor ward. Similar studies from [8][9][10] other tertiary institutions from different states in India in past 15 years reported MMR ranged between 270 and 974 per 1,00,000 live births (Table 4). 1,[6][7][8][9][10] Mukherjee et al 10 reported MMR of 1108, at a hospital in Bareilly, Uttar Pradesh, during their study period of 5 years.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we included only those cases which were given some kind of resuscitative measure in intensive care unit or in labor ward. Similar studies from [8][9][10] other tertiary institutions from different states in India in past 15 years reported MMR ranged between 270 and 974 per 1,00,000 live births (Table 4). 1,[6][7][8][9][10] Mukherjee et al 10 reported MMR of 1108, at a hospital in Bareilly, Uttar Pradesh, during their study period of 5 years.…”
Section: Discussionsupporting
confidence: 77%
“…9 Death of pregnant lady during transport to the higher center for specialty treatment has always been a matter of concern and it concludes that there is a shortage of wellequipped transport facility and trained personnel. 9,11,13,14,18,22 The present study was carried out at a higher tertiary care center and teaching institute which shears maximum burden of complicated referred cases from other hospitals.…”
Section: While Das R Et Al Singh R Et Al Palmentioning
confidence: 99%
“…[5] Maternal mortality is an indicator of the quality of obstetric care in a community, directly reflecting the utilization of healthcare services available. [6] One of the most important goals of the MDGs is to reduce the maternal mortality. It was in this context, this study was conducted with the objectives to assess the existing MMR and the causes of maternal mortality over a period of 3 years in a tertiary care hospital in Maharashtra.…”
Section: Introductionmentioning
confidence: 99%